Dietary diversity and associated factors among children aged 6–23 months in Indonesia - Rizky Sekartaji (W.B. Saunders, 2021)
Background: Optimum feeding practice is the key to determine development and growth among infants and young children. Dietary diversity is considered an indicator to assess nutritional adequacy. Objectives: This study aimed to determine the factors that associated with minimum dietary diversity types among children aged 6–23 months in Indonesia. Methods: Secondary data analysis was carried out for this study using the Indonesian Demographic and Health Survey (IDHS) 2017. The study was conducted with inclusion criteria in women of childbearing age with ages ranging from 15 to 49 years, having children aged 6–23 months, and living with respondents (n = 4861). Data obtained using a questionnaire with cross-sectional design approach. Chi-square test, and logistic regression test were used to measure the determinants of minimum dietary diversity. Results: The prevalence of children aged 6–23 months who received various foods was 3070 (63.15%) respondents. Age of child of 18–23 months [AOR = 5.88; 95% CI = 4.48–7.14], mother graduated from university level [AOR = 5.16; 95% CI = 2.07–12.89], access to maternal information on mass media (reading newspapers or magazines [AOR = 1.30; 95% CI = 1.10–1.55] and watching television [AOR = 1.56; 95% CI = 1.06–2.30]), and richest wealth quintile [AOR = 1.91; 95% CI = 1.32–2.75] significantly related to minimum dietary diversity in children aged 6–23 months in Indonesia. Conclusions: The current study revealed that minimum dietary diversity among Indonesian children remain related to education, mass media and socio-economic level. Practice implications: Pediatric nurses can play a critical role here by delivering the messages through educational outreach visits that focus on poor uneducated mother. © 2020 Elsevier Inc.